Stereoselective Total Synthesis of Arundinolides A and B - Chang, Caizhu; Geng, Jialin; Liu, Yinxin; Du, Yuguo; Liu, Jun; Dong, Zhi-Bing (Synthesis, 2020)
The efficient and enantioselective syntheses of arundinolides A and B have been accomplished for the first time from chiral pool methyl-2,3-O-isopropylidene-β-d-ribofuranoside and d-ethyl lactate. The key features of the total synthesis are intramolecular crotonyl migration and NaBH4-CuCl catalyzed regioselective reduction and cross-metathesis reaction.
Keywords: arundinolides; total synthesis; chiral pool; regioselective reduction; crotonyl migration